WATER HYACINTH: A POSSIBLE ALTERNATIVE RATE RETARDING NATURAL POLYMER USED IN SUSTAINED RELEASE TABLET DESIGN - Sabera eKhatun; Kumar Bishwajit Sutradhar (Frontiers Media S.A., 2014)
In recent years natural polymers have been widely used, because of their effectiveness and availability over synthetic polymers. In this present investigation matrix tablets of Metformin hydrochloride were formulated using Water hyacinth powder and its rate retardant activity was studied. Tablets were prepared using wet granulation method with 8% starch as granulating agent and 5%, 10%, 15%, 20%, 25% and 30% of Water hyacinth powder to the drug. In preformulation study, angle of repose, Carr's Index and Hausner ratio were calculated. Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and Scanning Electron Microscopy (SEM) studies were performed and no interactions were found between drug and excipients. Weight variation, friability, hardness, thickness, diameter, and in vitro release study were performed with the prepared matrix tablets. Dissolution studies were conducted using USP type II apparatus at a speed of 100 rpm at 37oC ± 0.5 temperature, for 8 hours. All the formulations comply with both BP and USP requirements, but among all the formulations F-1 (5% of Water hyacinth) was the best fitted formula. The drug release patterns were explained in different kinetic models such as Zero order, First order, Higuchi, Hixson Crowell and Korsmeyer-Peppas equations. The current investigation implies that Water hyacinth has the potential to be used as a rate-retarding agent in sustained release drug formulations.